How Youth-Serving Organizations Enable Acquaintance Molesters. (October 2014) - Boyle, Patrick
In recent years, some of the country's most prominent institutions have been ensnared in child sex abuse scandals. While each abuse incident features its own particular circumstances, institutions that have been the subject of these scandals have displayed similar patterns of organizational behavior that allowed molesting to occur and molesters to escape accountability. We can learn from those patterns to better understand and combat acquaintance molestation in youth-serving organizations. Although sex abuse is an inherent risk in youth work, American youth-serving organizations have responded to this risk largely on a case-by-case basis after abuse incidents have been revealed, rather than through proactive strategies to reduce the risk of abuse and to respond effectively to allegations. An examination of abuse scandals reveals common patterns of behavior among paid and volunteer staff in organizations that did not enact comprehensive, proactive strategies: Faith in the organiation blinded staff to the liklihood of abuse; organizations kept workers ignorant about the extent of the abuse problem; when abuse accusations arose, staff gave the benefit of the doubt to the adult; when abuse accusations were confirmed, staffers did not know how to respond; and not knowing how to resopnd, staff prioritized the protection of the organization. As a result, child molesters have been falsely exonerated or not held accountable, abused children have been disbelieved, and abuse has continued. These organizations inadvertently achieved the opposite of their missions: They enabled child molesters at the expense of children.